PERAN BHABINKAMTIBMAS DALAM MENCEGAH TINDAK PIDANA PENCURIAN KENDARAAN BERMOTOR DI WILAYAH HUKUM POLRESTA BOGOR KOTA - Divani Mareta (Advances in Police Science Research Journal, 2020)
This research is motivated by the increasing number of motor vehicle theft in the Bogor City Police jurisdiction. The high level of community activities in the city of Bogor makes the crime that happens to be high too. And the pattern of prevention which is prioritized by the National Police can be accepted by the community rather than the pattern of repression or repression. Writing this thesis uses a qualitative approach to the type of descriptive research. Data collection techniques with interviews, observations, and document review. There are primary and secondary data sources and the theory used to analyze is role theory. The results found that the role of Bhabinkamtibmas in preventing the theft of motorized vehicles in Bogor City City Police with the implementation of counseling to guard the vehicle by locking the handlebar or steering wheel, double locking, entrusting to the parking attendant, or entrusting to people who are close to the vehicle parked, in a place that is busy, or do not leave tickets or important letters on the vehicle and if possible monitored CCTV. The obstacles of Bhabinkamtibmas in counseling the prevention of motor vehicle theft due to the fact that there are still many people who are not aware or open of their vehicles, namely by parking their vehicles without locking the handlebar or not using double keys. This condition is worsened by the ease in which people get a vehicle with a little money to use a motorcycle, so that many people are not aware of the importance of protecting vehicles from theft. Minimize the number of obstacles that exist by providing guidance as well as guidance by the police regarding the issue of kamtibmas and services received by the community or groups. Counseling must be done to remote areas or reach out to the distribution of excellent services conducted by the bhabinkamtibmas about how to prevent motor vehicle theft must be anticipated.